Permanent pacemaker implantation after alcoholic septal ablation induced complete heart block: Long-term impact - André Grazina; Isabel Cardoso; António Fiarresga; Sílvia Aguiar Rosa; Pedro Garcia Brás; Vera Ferreira; José Miguel Viegas; Bárbara Lacerda Teixeira; Rúben Ramos; Lídia de Sousa; Mário Martins Oliveira; Ana Galrinho; et al. (Revista Portuguesa de Cardiologia, 2024)
Introduction and objectives: Patients with hypertrophic obstructive cardiomyopathy (HOCM) that remain symptomatic despite optimized medical therapy often undergo alcohol septal ablation (ASA). One of the most frequent complications is complete heart block (CHB), requiring a permanent pacemaker (PPM) in variable rates of up to 20% of patients. The long-term impact of PPM implantation in these patients remains unclear. This study aimed to evaluate the long-term clinical outcomes in patients who implant PPM after ASA. Methods: Patients who underwent ASA at a tertiary center were consecutively and prospectively enrolled. Patients with previous PPM or implantable cardio-defibrillator were excluded from this analysis. Patients with and without PPM implantation after ASA were compared based on their baseline characteristics, procedure data and three-year primary endpoint of composite of all-cause mortality and hospitalization and secondary endpoint of composite of all-cause mortality and cardiac cause hospitalization. Results: Between 2009 and 2019, 109 patients underwent ASA, 97 of whom were included in this analysis (68% female, mean age 65.2 years old). 16 patients (16.5%) required PPM implantation for CHB. In these patients, no vascular access, pacemaker pocket or pulmonary parenchyma complications were noted. The baseline characteristics of comorbidities, symptoms, echocardiographic and electrocardiographic findings were identical in the two groups, with higher mean age (70.6±10.0 years vs. 64.1±11.9 years) and lower beta-blocker therapy rate (56% vs. 84%) in the PPM group. Procedure-related data showed higher creatine kinase (CK) peaks in the PPM group (1692 U/L vs. 1243 U/L), with no significant difference in the alcohol dose. At three years after ASA procedure, there were no differences in the primary and secondary endpoints between the two groups. Conclusions: Permanent pacemaker after ASA induced CHB do not affect long term prognosis in hypertrophic obstructive cardiomyopathy patients. Resumo: Introdução e objetivos: Doentes com miocardiopatia hipertrófica obstrutiva (MCHO) sintomáticos apesar de terapêutica médica otimizada são frequentemente submetidos a ablação septal alcoólica (ASA). O bloqueio atrioventricular (BAV) completo é uma complicação frequente, requerendo implantação de pacemaker definitivo em taxas variáveis que podem ir até 20% dos doentes. O impacto a longo prazo da implantação de pacemaker nestes doentes permanente mal-esclarecido. Esta análise pretende avaliar os outcomes clínicos a longo prazo nestes doentes. Métodos: Doentes consecutivos submetidos a ASA num centro terciário foram incluídos e seguidos prospetivamente. Pacientes com pacemaker ou cardiodesfibrilhador prévio foram excluídos desta análise. Os doentes com e sem implantação de pacemaker após a ASA foram caracterizados e comparados relativamente aos endpoints primário (composto de mortalidade e hospitalização por todas as causas) e secundário (composto de mortalidade por todas as causas e hospitalização de causa cardíaca) a três anos. Resultados: Entre 2009 e 2019, 109 pacientes foram submetidos a ASA e 97 foram incluídos nesta análise (68% sexo feminino, idade media 65,2 anos). Implantaram pacemaker 16 doentes (16,5%) após a ASA por BAV completo. Não se registaram complicações vasculares, da loca ou parenquimatosas pulmonares. As características basais foram semelhantes entre os grupos, com maior idade média (70,6 ± 10,0 anos versus 64,1 ± 11,9 anos) e menor taxa de terapêutica beta-bloqueante (56% versus 84%) no grupo de pacemaker. Dados do periprocedimento revelaram maior pico de creatina cinase (CK) no grupo de pacemaker, sem diferença na dose de álcool usado. Aos três anos, os endpoints primário e secundário não mostraram diferenças entre os dois grupos. Conclusão: A implantação de pacemaker definitivo por BAV completo induzido por ablação septal alcoólica não afeta o prognóstico de pacientes com MCHO.